2011
DOI: 10.1007/s10973-011-1906-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the zirconia transformation on the thermal behavior of zircon–zirconia composites

Abstract: During a heating-cooling cycle, zirconia (ZrO 2 ) undergoes a martensitic transformation from monoclinic to tetragonal structure phases, which presents special hysteresis loop in the dilatometry curve at temperatures between 800 and 1100 °C. Monoclinic zirconia (m-ZrO 2 ) particles reinforced ceramic matrix composites not always present this behavior. In order to elucidate this fact a series of zircon-zirconia (ZrSiO 4 -ZrO 2 ) ceramic composites have been obtained by slip casting and characterized. The final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…This dissociation is known to be responsible for fracture toughness reinforcement by transformation toughening mechanism and micro cracks formation among other mechanisms [16,17]. Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This dissociation is known to be responsible for fracture toughness reinforcement by transformation toughening mechanism and micro cracks formation among other mechanisms [16,17]. Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…10 is well documented in literature. Zircon dissociated in silica and Zirconia producing the transformation toughening mechanism in Zirconia grains [16,17]. Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…240 − 288 GPa. Previous investigators have reported the Young's modulus (E) of zircon ceramics as 210 [38], 275 [39] and 288 GPa [26]. The zircon ceramics in this work are multiphase, i.e., crystalline oxides of zircon and monoclinic zirconia as well as non-crystalline phases of amorphous silica and additive glass.…”
Section: Mechanical Properties Of the Ceramicsmentioning
confidence: 71%
“…As the samples are annealed to a temperature of 500 °C, tetragonal ZrO 2 peaks begin to appear in both air and vacuum environments. Zirconia has a unique feature of the temperature-dependent reversibility of crystal phases thus the tetragonal ZrO 2 formed after annealing converts back to monoclinic ZrO 2 upon cooling the samples down to room temperature (Figure a). In the air, this phenomenon of phase transitions typically results in severe cracking because of 4–5% volume difference between two phases (Figure c).…”
Section: Synthesis Of Nanoporous Structuresmentioning
confidence: 99%